2011
DOI: 10.1186/1475-2891-10-93
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeinated and decaffeinated coffee on biological risk factors for type 2 diabetes: a randomized controlled trial

Abstract: BackgroundCoffee consumption has been associated with a lower risk of type 2 diabetes in prospective cohort studies, but the underlying mechanisms remain unclear. The aim of this study was to evaluate the effects of regular and decaffeinated coffee on biological risk factors for type 2 diabetes.MethodsRandomized parallel-arm intervention conducted in 45 healthy overweight volunteers who were nonsmokers and regular coffee consumers. Participants were assigned to consumption of 5 cups (177 mL each) per day of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
135
5
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(159 citation statements)
references
References 29 publications
15
135
5
4
Order By: Relevance
“…In this randomized controlled trial with caffeinated and decaffeinated coffee interventions, we did not find evidence of a consistent effect on SHBG levels in overweight men or women. This contrasts with the beneficial effects of coffee consumption on adiponectin and fetuin-A levels previously reported in this trial [9], suggesting that the SHBG level is not the major intermediate of the putative effect of coffee consumption on a lower risk of T2DM. Our findings necessitate further examination in a larger intervention trial of the effects of coffee on sex hormones to elucidate if this is a potential intermediary …”
Section: Discussioncontrasting
confidence: 54%
“…In this randomized controlled trial with caffeinated and decaffeinated coffee interventions, we did not find evidence of a consistent effect on SHBG levels in overweight men or women. This contrasts with the beneficial effects of coffee consumption on adiponectin and fetuin-A levels previously reported in this trial [9], suggesting that the SHBG level is not the major intermediate of the putative effect of coffee consumption on a lower risk of T2DM. Our findings necessitate further examination in a larger intervention trial of the effects of coffee on sex hormones to elucidate if this is a potential intermediary …”
Section: Discussioncontrasting
confidence: 54%
“…Published intervention trials include comparisons of coffee consumption versus abstention [9], caffeinated versus decaffeinated coffee [10,11] or pure caffeine [12], coffees differing in brewing type [13], or coffees enriched or reduced in special coffee constituents [14]. The roasting process has an important impact on the content of coffee constituents [15,16].…”
Section: Introductionmentioning
confidence: 98%
“…This study also showed that the administration of caffeine was able to control the catecholamine levels (adrenaline and noradrenaline) in this group, reducing them up to 124% when comparing to the values of pre-consumption and further decreased sympathetic nervous system stimulation. Wedick et al (2011) evaluated the effect of the consumption of 5 cups of coffee (caffeinated and decaffeinated) for 8 weeks, over DMT2 risk factors, in 45 men over weighed. No alteration was observed in the following parameters: ISI, oral glucose tolerance test (OGTT) and insulin secretion.…”
Section: Resultsmentioning
confidence: 99%
“…On long-term, studies demonstrated that caffeine did not alter (Wedick et al, 2011) or increased glucose tolerance (Guarino et al, 2013) and insulin sensibility (Yamauchi et al, 2010).…”
Section: Caffeine Biological Effect In the Organismmentioning
confidence: 99%